Pemenuhan HAM Melalui Kebijakan Izin Tinggal Terpaksa Terhadap WNA Di Bali Pada 2020-2021 - Hilda Dermaya Orifia; de Fretes, Christian H. J.; W. Nau, Novriest Umbu (Administraus, 2025)
This research analyzes efforts to fulfill human rights through the forced stay policy for foreign nationals in Bali during the COVID-19 pandemic in 2020-2021. The pandemic caused a significant decline in Bali's tourism sector and impacted the mobility of foreigners who were forced to stay longer due to lockdowns. The Indonesian government issued Minister of Law and Human Rights Regulation Number 8 of 2020 as a form of legal protection that provides foreigners with certainty of residence permits in forced circumstances. This study uses a classical liberalism theory approach and descriptive qualitative research method to assess the government's role in ensuring the fulfillment of human rights, both for Indonesian citizens and foreigners. The findings show that this policy is not only a form of commitment to human rights, but also reflects the government's active response in maintaining legal stability in the midst of an emergency situation. However, the implementation of this policy faces administrative challenges and inter-agency coordination, which demands increased transparency and efficiency of services.